Early Childhood Social Interaction in Sports at Satria Pushbike Community - Davifeda Gibran Daffa; Fery Darmanto (Universitas Negeri Semarang, 2026)
Early childhood social development is a crucial foundation for future well‑being and success. However, increased screen time and reduced face‑to‑face interaction pose serious challenges. This study aims to describe the forms, dynamics, and facilitative roles of early childhood social interaction in pushbike activities at the Satria Pushbike Purwokerto Community. This research employed a descriptive qualitative approach with mixed methods. Subjects were 15 parents and 1 coach. Data collection used observation, semi‑structured interviews, and documentation. Quantitative analysis used SPSS and qualitative analysis used NVivo. Descriptive statistics showed that the average responses fell into the “Often” category (frequency 99) and “Very Often” category (frequency 93). NVivo analysis produced 9 project maps confirming that parental roles and emotional support are the most dominant factors. Pushbike activities within the community function as an effective social laboratory for developing children’s social interaction, with success depending on synergy between parents, coaches, and the peer environment. This study provides empirical evidence for community‑based sports programs oriented toward social interaction in Indonesia.